Military criminal jurisdiction: an institution in crisis (2015)
The following paper aims to get an appropriate understanding of the military criminal justice system and of the criminal privilege for the Army and the Police forces, derived from the article 221 from the Colombian Political Constitution of 1991, because, as all penal jurisdictions, it was made not to give privilege to the people with a particular condition or dignity, but to preserve the civil servant condition of their positions. Therefore, it is necessary to affirm emphatically that the military criminal justice system could be specialfrom the standard criminal justice system, but cannot be uneven or biased, because if that happens, it is no longer justice.